2021
DOI: 10.1590/1517-8692202127012020_0066
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Equations to Estimate Visceral Adipose Tissue in Military Men

Abstract: Introduction It has been suggested that visceral adipose tissue (VAT) is associated with several non-communicable chronic diseases, but measuring it is difficult. Thus, anthropometry could be used because is easily applied in clinical practice. Objectives The present study aimed to develop and validate VAT estimation equations (Eq) in military men. Methods The sample consisted of 409 (mean age, 36.5 ± 6.7 years) military men in the Brazilian Army (BA) divided into an equation group (EG) ( n = 270; mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Interestingly, we found predicted VAT accounted for more variance in seven of the examined blood‐based biomarkers related to systemic inflammation in men and nine in women when compared to BMI, WC, WHR and WHtR. In particular, equations by da Rosa et al, 11 Eastwood et al, 12 Goel et al 13 and So et al 15 demonstrated potential use as tools to characterise metabolic health. This suggests a role for equations in assessing VAT levels and that these might be used to identify high‐risk subjects in clinical care and health‐related research.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Interestingly, we found predicted VAT accounted for more variance in seven of the examined blood‐based biomarkers related to systemic inflammation in men and nine in women when compared to BMI, WC, WHR and WHtR. In particular, equations by da Rosa et al, 11 Eastwood et al, 12 Goel et al 13 and So et al 15 demonstrated potential use as tools to characterise metabolic health. This suggests a role for equations in assessing VAT levels and that these might be used to identify high‐risk subjects in clinical care and health‐related research.…”
Section: Discussionmentioning
confidence: 71%
“…Predicted visceral adipose tissue was defined using a selection of 10 existing equations based on a range of anthropometric measures and other variables (Table 1). 9–15 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations